miR-663a inhibits tumor growth and invasion by regulating TGF-β1 in hepatocellular carcinoma - Chengshuo Zhang (BMC Cancer, 2018)
Abstract Background The dysregulation of miR-663a is frequently observed in many human cancers. However, the functional role and precise mechanism of miR-663a have been controversial in hepatocellular carcinoma (HCC) and need to be studied in depth. Methods The expression of miR-663a was detected in human cell lines and HCC tissues by quantitative RT-PCR (qRT-PCR), and data from the Cancer Genome Atlas (TCGA). Cell proliferation was investigated using MTS, EdU, colony formation assays, and xenograft animal experiments, and the cell invasion capacity was evaluated using the transwell assay. The target gene of miR-663a was identified by qRT-PCR, Western blot, and dual-luciferase reporter assays. The clinicopathological features of miR-663a and the correlation between miR-663a and TGF-β1 expression were also investigated in the clinical samples of HCC. Results miR-663a was significantly downregulated in HCC cells relative to immortal normal liver cells, as indicated using qRT-PCR, and the lower expression of miR-663a was also confirmed in HCC tissue samples and the data from TCGA. The expression of miR-663a in HCC tissue samples was statistically significantly associated with size and the number of tumors. In addition, the upregulation of miR-663a inhibited the proliferation and invasion of HCC cells in vitro. Further study showed that miR-663a directly targeted transforming growth factor beta 1 (TGF-β1) to suppress HCC invasion, and that the inhibitory effect of miR-663a on cell invasion could be regulated by TGF-β1. In vivo studies showed that miR-663a significantly inhibited tumor growth. A negative correlation between miR-663a and TGF-β1 expression was also confirmed from the clinical samples of HCC. Conclusions miR-663a acts as a tumor suppressor and exerts a substantial role in inhibiting the proliferation, invasion, and tumorigenesis of HCC by regulating TGF-β1 in vitro and in vivo. These observations indicate that miR-663a may be a suitable diagnostic, therapeutic, and prognostic target for the treatment of HCC.